2017
DOI: 10.1080/00222895.2017.1407287
|View full text |Cite
|
Sign up to set email alerts
|

Learning New Letter-like Writing Patterns Explicitly and Implicitly in Children and Adults

Abstract: A handwriting task was used to test the assumption that explicit learning is dependent on age and working memory, while implicit learning is not. The effect of age was examined by testing both, typically developing children (5-12 years old, n = 81) and adults (n = 27) in a counterbalanced within-subjects design. Participants were asked to repeatedly write letter-like patterns on a digitizer with a non-inking pen. Reproduction of the pattern was better after explicit learning compared to implicit learning. Age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…On the other hand, van Abswoude et al (Van Abswoude et al, 2020; did not find an effect of either verbal or visuospatial working memory on motor performance or learning following implicit or explicit learning. Similar results were shown by Jongbloed-Pereboom et al (2018). In addition, Jongbloed-Pereboom et al ( 2017) showed a role for visuospatial working memory capacity in both implicit and explicit groups.…”
Section: Individual Differencessupporting
confidence: 67%
“…On the other hand, van Abswoude et al (Van Abswoude et al, 2020; did not find an effect of either verbal or visuospatial working memory on motor performance or learning following implicit or explicit learning. Similar results were shown by Jongbloed-Pereboom et al (2018). In addition, Jongbloed-Pereboom et al ( 2017) showed a role for visuospatial working memory capacity in both implicit and explicit groups.…”
Section: Individual Differencessupporting
confidence: 67%
“…Although letters in general have been extensively used as a primary data source in research for centuries (Harris, 2002), researchers have only recently started to use letter writing as a way to generate self-reflexive data on people's lived experiences (Ahearn, 2001;Kralik et al, 2000;Rautio, 2009). Letter writing is a methodology that has been used in a range of studies to enable contributions from hard-to-reach participants or those with limited accessibility (Brown, 2014;Davidson and Birmingham, 2001;Davis, 1967;Dunn, 2000;Epston, 2009;Grana et al, 2001;Jiwa and Burr, 2002;Jolly, 2011;Jongbloed-Pereboom et al, 2018;Kelly and Waring, 2018;Kirkhorn and Airth-Kindree, 2010;Muzumdar et al, 2020;Penny and Malpass, 2019;Rancour and Brauer, 2003;Seddon, 2018;Sommer, 1958;Thompson et al, 2017).…”
Section: Methods and Ethicsmentioning
confidence: 99%
“…While letters in general have been used as data source in historical, sociological and literary research for centuries (Harris, 2002), researchers have only recently started to use letter-writing between a researcher and a research participant as a way to generate self-reflexive data on people’s lived experiences (Ahearn, 2001; Kralik et al, 2000; Rautio, 2009). Letter writing is a methodology that has been used in a range of studies to enable research participants to participate in research projects that their circumstances for whatever reason don’t allow them to participate in person (Brown, 2014; Davidson & Birmingham, 2001; Davis, 1967; Dunn, 2000; Epston, 2009; Grana et al, 2001; Jiwa & Burr, 2002; Jolly, 2011; Jongbloed-Pereboom et al, 2018; Kelly & Waring, 2018; Kirkhorn & Airth-Kindree, 2010; Muzumdar et al, 2020; Penny & Malpass, 2019; Rancour & Brauer, 2003; Seddon, 2018; Sommer, 1958; Thompson et al, 2017).…”
Section: Methods and Ethicsmentioning
confidence: 99%
“…The literature on Covid-19 in prison settings is emerging at the time of writing, with new studies published all the time, although these tend to be quite limited (Johnson et al, 2021). The majority of the emerging literature on Covid-19 in prison settings is health focused (Kakimoto et al, 2020;Okano & Blower, 2020;Vose et al, 2020) and often focused on different protocols and precautions that can, should and have been utilised to minimise the transmission of the virus in the prison setting (Burki, 2020;de Carvalho et al, 2020;Jones & Tulloch, 2020;Montoya-Barthelemy et al, 2020;Solis et al, 2020;Vose et al, 2020;Wang et al, 2020). Robinson et al (2020) have highlighted the impacts of digital inequalities in the face of Covid-19's outbreak, and prisoners and those held in detention centres, as they discuss, are at higher risk of experiencing the impacts of these digital inequalities.…”
Section: Covid-19 In Prison Settingsmentioning
confidence: 99%